2020
DOI: 10.35848/1347-4065/ab6862
|View full text |Cite
|
Sign up to set email alerts
|

High interfacial quality metal-oxide-semiconductor capacitor on (111) oriented 3C-SiC with Al2O3 interlayer and its internal charge analysis

Abstract: Metal-oxide-semiconductor (MOS) capacitors with various gate dielectrics were fabricated on (111) oriented n-type 3C-SiC. Deposited SiO2 by sputtering without an interlayer (IL) and thermally grown SiO2 show deteriorated capacitance–voltage (C–V) characteristics and high interface trap density (Dit) over 1011–1012 cm−2 eV−1. By inserting an IL, C–V and leakage current characteristics are improved. In particular, an atomic layer deposited (ALD) Al2O3-IL is suitable for 3C-SiC, which successfully achieved low Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…© 2022 The Japan Society of Applied Physics listed the D it values of the MOS capacitors calculated using a high and low-frequency C-V (high-low) method in our former study, and the magnitude correlation is the same as the result from SS. 16) It should be noted that D it values evaluated from SS are 10-30 times higher than those from the high-low method for both gate stacks. It is a common phenomenon for SiC gate stacks, and the reason is the underestimation (better than the actual value) of the high-low method.…”
Section: -3mentioning
confidence: 78%
See 3 more Smart Citations
“…© 2022 The Japan Society of Applied Physics listed the D it values of the MOS capacitors calculated using a high and low-frequency C-V (high-low) method in our former study, and the magnitude correlation is the same as the result from SS. 16) It should be noted that D it values evaluated from SS are 10-30 times higher than those from the high-low method for both gate stacks. It is a common phenomenon for SiC gate stacks, and the reason is the underestimation (better than the actual value) of the high-low method.…”
Section: -3mentioning
confidence: 78%
“…As an alternative method, we have succeeded in fabricating 3C-SiC MOS capacitors using sputter-deposited SiO 2 /plasma oxidized interlayer (plasma oxi.-IL) and SiO 2 /Al 2 O 3 -IL. 16) The process temperature is as low as about 500 °C, and we achieved outstanding C-V characteristics with low D it and narrow hysteresis. This low-temperature process is preferable for the on-chip hetero-integration between Si and 3C-SiC.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…So far, it has been reported that a stable 3C-SiC intermediate layer can be introduced in between GaN and Si to suppress the crack generation and enhance the crystal quality of the GaN film on Si substrate [14], [17]- [20]. Owing to the above fact, a thick nitride layer can be grown on Si by introducing a 3C-SiC intermediate layer [14], [20].…”
Section: Introductionmentioning
confidence: 99%